A partial equilibrium model of the Malawi maize commodity market - Mapila, Mariam A.T.J.; Kirsten, Johann F.; Meyer, Ferdinand; Kankwamba, Henry (International Food Policy Research Institute, 2013)
This paper presents a model of the Malawi maize commodity market that is developed for use as a policy analysis tool. The model captures national and local maize market dynamics and the linkages existing within the maize market in the country. This research has been undertaken in order to provide policy makers with a robust tool which can be used to simulate the impact of policy changes on markets and households.